Rediscovery, hosts and systematics of Holothuriophilus trapeziformis Nauck, 1880 (Crustacea, Brachyura, Pinnotheridae) - Campos, Ernesto; Peláez-Zárate, Víctor Arturo; Solís-Marín, Francisco A. (Zootaxa, 2012)
The type species of Holothuriophilus Nauck, 1880, H. trapeziformis Nauck, 1880 is rediscovered in the type locality,Mazatlán, Sinaloa, Mexico and in a new locality, Zihuatanejo Bay, Guerrero, Mexico. The generic diagnostic features in-clude a smooth, transversally elongated carapace, that is broader than long, widest portion anterior to middle portion andwith a cristate anterolateral margin; basal antennal article lacking a conical protuberance; third maxilliped with fusedischium and merus, spoon-shaped dactyl larger than subtrapezoidal propodus which is subequal in length to the carpus;abdomen with six somites and free telson. Hosts recorded for H. trapeziformis include the holothurids Holothuria inornataSemper, 1868, H. lubrica Selenka, 1867 and H. kefersteini Selenka, 1867 (=Paraholothuria riojai Caso, 1964), however,only the former is herein confirmed. Holothuriophilus trapeziformis can be separated from its eastern Pacific congener H.pacificus (Poeppig, 1836) because the fingers of the chela meet when closed instead of leaving a gape as in the latter species.La especie tipo de Holothuriophilus Nauck, 1880, H. trapeziformis Nauck, 1880, fue redescubierta en la localidad tipo,Mazatlán, Sinaloa y en una nueva localidad, Zihuatanejo, Guerrero, México. Las características diagnósticas incluyen: ca-parazón transversalmente alargado, más ancho que largo, su mayor amplitud anterior a la parte media, liso, y con el mar-gen anterolateral cristado; artejo basal de la antena carece de una protuberancia cónica; tercer maxilipedio con el isquio ymero fusionado, dáctilo de forma acucharado, más largo que el subtrapezoidal propodio el cual es subigual en longitud alcarpo, y el abdomen de seis somitos y telson libre. Los huéspedes registrados para esta especie incluyen a Holothuria in-ornata Semper, 1868, H. lubrica Selenka, 1867 y H. kefersteini Selenka, 1867 (=Paraholothuria riojai Caso, 1964), perosólo la primer especie es aquí confirmada. Holothuriophilus trapeziformis puede ser separado de su congénere del Pacíficooriental, H. pacificus (Poeppig, 1836), debido a que los dedos de la quela se juntan al cerrarse en vez de dejar una abertura como en la última especie.